Analysis of Marketing Strategies in Increasing Sales at Ska Motor Dealers in the Duchy of Majalengka Regency - Mila Meriska; Ryan Feryana Kurniawan (Journal of Bussines Management Basic, 2023)
This study analyzes the focus of the marketing strategy problems that exist in the Ska Motor Dealer of the Majalengka Regency. The purpose of this research is to find out the implementation and problems of marketing strategy at the Ska Motor Dealer of the Kadipaten Majalengka. The approach uses a qualitative method approach. The sampling technique was carried out by purpsive sampling technique. Informants are branch heads and consumers. The research data used the Milles and Huberman model with the steps used data reduction, data display and conclusion. Test the validity of the data using triangulation techniques. The marketing strategy used by the Ska Motor Dealer Majalengka Branch includes the 7Ps (product, price, place, promotion, people, physical evidence, and process). The results of the marketing strategy research at the Ska Motor Dealer, Majalengka Kadipaten Branch, show that the dimensions of the product are seen in the quality of the product is good, the price dimension is seen in the pricing is quite good and the price discount is quite good but not optimal, the dimensions of the place seen from the location are good, the dimensions of the promotion can be seen in direct marketing, advertising and personal selling are good enough but there are some that are not optimal in promotion, the people dimension seen from the customer service is good, the physical evidence dimension is seen in quite good facilities, the process dimension is seen from good communication. Ska Motor Dealers in the Duchy of Majalengka to further improve their sales promotions and hold more discounted prices